Monalizumab: inhibiting the novel immune checkpoint NKG2A. Issue 1 (17th October 2019) - van Hall, Thorbald; André, Pascale; Horowitz, Amir; Ruan, Dan Fu; Borst, Linda; Zerbib, Robert; Narni-Mancinelli, Emilie; van der Burg, Sjoerd H.; Vivier, Eric
Abstract : The implementation of immune checkpoint inhibitors to the oncology clinic signified a new era in cancer treatment. After the first indication of melanoma, an increasing list of additional cancer types are now treated with immune system targeting antibodies to PD-1, PD-L1 and CTLA-4, alleviating inhibition signals on T cells. Recently, we published proof-of-concept results on a novel checkpoint inhibitor, NKG2A. This receptor is expressed on cytotoxic lymphocytes, including NK cells and subsets of activated CD8 + T cells. Blocking antibodies to NKG2A unleashed the reactivity of these effector cells resulting in tumor control in multiple mouse models and an early clinical trial. Monalizumab is inhibiting this checkpoint in human beings and future clinical trials will have to reveal its potency in combination with other cancer treatment options.